2018
DOI: 10.2340/00015555-3001
|View full text |Cite
|
Sign up to set email alerts
|

Granular IgA Deposits in the Skin of Patients with Coeliac Disease: Is it Always Dermatitis Herpetiformis?

Abstract: Coeliac disease is an immune-mediated enteropathy driven by gluten, which can be associated with dermatitis herpetiformis. The presence of granular IgA deposits, detected by direct immunofluorescence, is the hallmark of dermatitis herpetiformis; nevertheless, IgA deposits have also been demonstrated in healthy skin of patients with coeliac disease. The main objective of this study was to investigate whether IgA deposits could be found in the skin of patients with coeliac disease who have non-dermatitis herpeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…Interestingly in this respect, codistribution of tissue transglutaminase and tissue-bound IgA in jejunum of patients with DH was reported in the meeting abstract [18]. IgA deposits at the DEJ of perilesional skin with DIF can also be found in coeliac patients with inflammatory skin diseases different from DH and, therefore, could even be considered as a marker of coeliac disease [19]. Interestingly, analysing 16 DH patients with both ELISA and immunoblot, we noticed certain discrepancies between the results of DIF and testing for circulating autoantibodies incriminated to be DH serum biomarkers.…”
Section: Direct Immunofluorescence: Present and Futurementioning
confidence: 99%
“…Interestingly in this respect, codistribution of tissue transglutaminase and tissue-bound IgA in jejunum of patients with DH was reported in the meeting abstract [18]. IgA deposits at the DEJ of perilesional skin with DIF can also be found in coeliac patients with inflammatory skin diseases different from DH and, therefore, could even be considered as a marker of coeliac disease [19]. Interestingly, analysing 16 DH patients with both ELISA and immunoblot, we noticed certain discrepancies between the results of DIF and testing for circulating autoantibodies incriminated to be DH serum biomarkers.…”
Section: Direct Immunofluorescence: Present and Futurementioning
confidence: 99%
“…However, Donaldson et al observed that granular IgA deposits could be also detected in the non-affected skin of DH patients (114). More intriguingly, Cannistraci et al documented eTG/IgA co-localization in the papillary dermis, at the dermal-epidermal junction and in the vessel walls of coeliac patients without skin manifestations both before and during a GFD (10, 117, 118). It is also worth of mention that disappearance of eTG/IgA deposits from the skin occurs only in a subset of patients despite a long and strict GFD and no active skin rash, and takes much longer than serum autoantibodies or immune complexes (76, 119).…”
Section: Pathogenesismentioning
confidence: 99%
“…On this point, a recent paper from our group reported a case-series of six celiac patients presenting with skin diseases different from DH, such as contact eczema, dermatophytosis, granuloma annulare, pytiriasis rosea, lichenoid dermatitis, and psoriasis. Notably, all these patients showed a granular deposit of IgA at the dermal-epidermal junction and/or at the papillary tips (10). As previously mentioned, Cannistraci et al observed granular IgA deposits in the healthy skin of nine celiac patients without any cutaneous manifestation (117).…”
Section: Diagnosis Of Dermatitis Herpetiformismentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, histopathological examination of skin lesion helps in correct diagnosis, which often can be a dermatosis other than DH [62]. A recent study described six patients with celiac disease with various inflammatory dermatoses who also showed granular IgA deposits in immunofluorescence specimens [63]. However, no evidence of clinical DH and coexistent TG3 deposits were seen, suggesting that the IgA findings were not representative of typical DH.…”
Section: Diagnosis Of Dermatitis Herpetiformismentioning
confidence: 99%